Gambaran Religiusitas Mahasiswa Kristen Protestan di Universitas Kristen X - Dewi, Natasya Kemala; Garey, Evans (Sekolah Tinggi Teologi Tawangmangu, 2025)
This study aims to describe the religiosity of Protestant Christian students at Christian University X with a descriptive quantitative approach, using the Duke University Religion Index (DUREL) scale. Participants were 339 students with an age range of 18-25 years. The results of the study indicate that the majority of students have a high level of religiosity. A total of 80.8% of students are active in religious activities in groups/organizations (Organizational Religious Activity), as many as 58.4% of students are active in personal religious activities (Non-Organizational Religious Activity). And as many as 85% of students have high intrinsic motivation (Intrinsic Religiosity). Based on these findings, it shows that students are not only involved in religious activities in organizations or personally, but also have strong religious motivation and commitment that comes from within themselves. This study has implications for the development of literature on the religiosity of Protestant Christian students using the DUREL scale in Indonesia. In addition, the results of the study can be used as input for universities and spiritual institutions to strengthen faith development programs, not only emphasizing group activities but also personal and deepening internal motivation in religion. AbstrakPenelitian ini bertujuan menggambarkan religiusitas mahasiswa Kristen Protestan di Universitas Kristen X dengan pendekatan kuantitatif deskriptif, menggunakan skala Duke University Religion Index (DUREL). Partisipan berjumlah 339 mahasiswa dengan rentang usia 18-25 tahun. Hasil penelitian menunjukkan bahwa mayoritas mahasiswa memiliki tingkat religiusitas yang tinggi. Sebanyak 80,8% mahasiswa aktif dalam aktivitas keagamaan secara berkelompok/organisasi (Organizational Religious Activity), sebanyak 58,4% mahasiswa aktif dalam aktivitas keagamaan pribadi (Non-Organizational Religious Activity). Dan sebanyak 85% mahasiswa memiliki motivasi intrinsik yang tinggi (Intrinsic Religiosity). Berdasarkan temuan ini, menunjukkan bahwa mahasiswa tidak hanya terlibat dalam kegiatan keagamaan secara organisasi maupun secara personal, tetapi juga memiliki motivasi dan komitmen beragama yang kuat yang berasal dari dalam dirinya sendiri. Penelitian ini berimplikasi pada pengembangan literatur mengenai religiusitas mahasiswa Kristen Protestan dengan menggunakan skala DUREL di Indonesia. Selain itu juga, hasil penelitian dapat digunakan sebagai masukan bagi Universitas dan lembaga kerohanian untuk memperkuat program pembinaan iman, bukan hanya menekankan pada kegiatan secara berkelompok tetapi juga secara personal dan pendalaman motivasi internal dalam beragama.